Стратегия формирования городских развозочных маршрутов на оперативный период с учетом неравномерности распределения спроса на специфические грузы - Нагорный, Е. В.; Музылев, Д. А. (Eastern-European Journal of Enterprise Technologies, 2020)
Strategy formation of delivery routes within the city taking inequality demand from customers during the operational period of work is propose